Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4047/jap.2014.6.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of endodontically treated maxillary premolars restored by silorane-based composite with or without fiber or nano-ionomer

Abstract: PURPOSEThis in vitro study investigated the fracture resistance of endodontically treated premolars restored using silorane- or methacrylate-based composite along with or without fiber or nano-ionomer base.MATERIALS AND METHODSNinety-six intact maxillary premolars were randomly divided into eight groups (n = 12). G1 (negative control) was the intact teeth. In Groups 2-8, root canal treatment with mesio-occlusodistal preparation was performed. G2 (positive control) was kept unrestored. The other groups were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…One experienced operator made all preparations. Measurements were made with a digital caliper (Mitutoyo Digimatic; Mitutoyo, Kawasaki, Japan) with 0.1‐mm sensitivity for proper and accurate standardization of cavity dimensions …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One experienced operator made all preparations. Measurements were made with a digital caliper (Mitutoyo Digimatic; Mitutoyo, Kawasaki, Japan) with 0.1‐mm sensitivity for proper and accurate standardization of cavity dimensions …”
Section: Methodsmentioning
confidence: 99%
“…Measurements were made with a digital caliper (Mitutoyo Digimatic; Mitutoyo, Kawasaki, Japan) with 0.1-mm sensitivity for proper and accurate standardization of cavity dimensions. 30 The teeth were numbered from 1 to 120 and then randomly distributed into ten experimental groups of 12 teeth each using random numbers generated by a computer program. ANOVA analysis of average size (BL and MD) values of teeth in the ten groups showed no significant differences between the groups (p > 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…[65,66] evaluated fiber-reinforced composite resin restorations and concluded that using polyethylene fiber under composite restorations in root-filled teeth with MOD preparations significantly increases fracture strength, reduces leakage in class 2 cavities [67], and strengthens microtensile bonding to dentin [68]. Furthermore, fiber reinforcement between the restorative resin and dentin changes the fracture line, causes repairable fractures, saving the remaining tooth structure [65,66,68], and increases the restorability of methacrylate-based composite resin-restored teeth after failure [69]. Although fiber-reinforced composite restorations are prone to aging due to exposure to the oral environment and the mechanical properties may deteriorate over time [70], one of the great benefits of this technology is the possibility of extending functional survival by repairing restorations in the oral cavity [71].…”
Section: Fiber-reinforced Composite Materialsmentioning
confidence: 99%
“…Compressive loading during the fracture resistance test may be distributed throughout the restored tooth by different materials. Thus, Shafiei et al (2014) [80] suggested covering the cusps with an amalgam and composite resin combination and found no difference between the group receiving direct composite coverage and the one undergoing amalgam-based composite restoration. Nevertheless, direct cusp coverage with composite restoration appears to be a reliable method in extensive cavities [44,73].…”
Section: Fiber-reinforced Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation